Academic Resilience of Student at SMA Negeri 2 Padang Panjang - Lara Amanda Dwidjo; Zadrian Ardi (Jurnal Neo Konseling, 2023)
Students who are studying are faced with various kinds of pressure, difficulties, challenges or poor learning outcomes. In this situation resilience is needed by students to follow learning at school. Students who have high academic resilience are able to make difficult environments and situations a source of motivation to rise from adversity. The purpose of this study was to describe the academic resilience of students at SMA Negeri 2 Padang Panjang in terms of the aspects of perseverance, reflecting and adaptive help-seeking and negative affect and emotional responses. This type of research is descriptive research with quantitative methods. The population of this study were all students of grades X, XI and XII of SMA Negeri 2 Padang Panjang totaling 836 students with a sample of 275 students who were selected using the proportional stratified random sampling technique. Data collection used an academic resilience questionnaire with a Likert scale model, data processing used the Microsoft Excel application. The overall results of this study indicate that the academic resilience of students at SMA Negeri 2 Padang Panjang is in the high category with a percentage of 61.82%. If viewed from the aspect of persistence (persistence) is in the high category with a percentage of 63.6%, aspects of reflecting and adaptive help-seeking (reflection and adaptive seeking help) are in the high category with a percentage of 59.6%, negative affect and emotional aspects response (negative influence and emotional response) is in the high category with a percentage of 54.9%.